2003
DOI: 10.1007/s11664-003-0141-z
|View full text |Cite
|
Sign up to set email alerts
|

A study on interfacial reactions between electroless Ni-P under bump metallization and 95.5Sn-4.0Ag-0.5Cu alloy

Abstract: Even though electroless Ni-P and Sn-Ag-Cu solders are widely used materials in flip-chip bumping technologies, interfacial reactions of the ternary Cu-NiSn system are not well understood. The growth of intermetallic compounds (IMCs) at the under bump metallization (UBM)/solder interface can affect solder-joint reliability, so analysis of IMC phases and understanding their growth kinetics are important. In this study, interfacial reactions between electroless Ni-P UBM and the 95.5Sn-4.0Ag-0.5Cu alloy were inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
51
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(55 citation statements)
references
References 2 publications
4
51
0
Order By: Relevance
“…Jeon et al reported the formation of (Cu,Ni) 6 Sn 5 and (Ni,Cu) 3 Sn 4 IMCs at the interface between the Sn-4.0Ag-0.5Cu solder and electroless Ni-P layer. 15) Ho et al investigated the effect of a small perturbation in the Cu concentration in the reaction between Sn-3.9Ag-xCu solders (x ¼ 0:2 $ 3:0 in mass%) and Ni layer during a liquid-solid reaction at 250 C. 16) They reported that the slight variation in Cu concentration produced completely different reaction products. Generally, the thickness of the IMC layer at the interface between the solder and substrate is very important in determining the reliability of the whole package because an excessively thick IMC layer is sensitive to stress and sometimes provides initiation sites and paths for the propagation of cracks.…”
Section: Methodsmentioning
confidence: 99%
“…Jeon et al reported the formation of (Cu,Ni) 6 Sn 5 and (Ni,Cu) 3 Sn 4 IMCs at the interface between the Sn-4.0Ag-0.5Cu solder and electroless Ni-P layer. 15) Ho et al investigated the effect of a small perturbation in the Cu concentration in the reaction between Sn-3.9Ag-xCu solders (x ¼ 0:2 $ 3:0 in mass%) and Ni layer during a liquid-solid reaction at 250 C. 16) They reported that the slight variation in Cu concentration produced completely different reaction products. Generally, the thickness of the IMC layer at the interface between the solder and substrate is very important in determining the reliability of the whole package because an excessively thick IMC layer is sensitive to stress and sometimes provides initiation sites and paths for the propagation of cracks.…”
Section: Methodsmentioning
confidence: 99%
“…Especially, the reactions between Ni(P)|Au-coated soldering pads and solders have been studied extensively. [8][9][10][11][12][13][14][15][16][17] Likewise, the cracking of interconnections soldered on the Ni(P) metallization has also been reported in these papers and the occurrence of the failure is typically explained by the oxidation or contamination of the plating bath that affects the quality of the metallization.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Fig. 2c 15 Ho et al investigated the effect of a small perturbation in the Cu concentration on the reaction between four Sn-3.9Ag-xCu solders (x = 0.2 wt.% to 3.0 wt.%) and a Ni layer during a liquid-solid reaction at 523 K. 16 They reported that a slight variation in the Cu concentration produced completely different reaction products. Generally, the thickness of the IMC layer at the interface between the solder and substrate is very important in determining the reliability of the whole package, because an excessively thick IMC layer is sensitive to stress and sometimes provides initiation sites and paths for crack propagation.…”
Section: Resultsmentioning
confidence: 99%